The dilemmas of reason and progress in a field in ruins: The doctrine of Saint-Simon: an exposition - Martínez Mesa, Francisco (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
doi: http://dx.doi.org/10.20318/eunomia.2016.3294